2017
DOI: 10.1080/08916934.2017.1280029
|View full text |Cite
|
Sign up to set email alerts
|

Clonally expanded cytotoxic CD4+T cells and the pathogenesis of IgG4-related disease

Abstract: IgG4-related disease (IgG4-RD) is a systemic condition of unknown cause characterized by highly fibrotic lesions, with dense lymphoplasmacytic infiltrates containing a preponderance of IgG4-expressing plasma cells. CD4+ T cells and B cells constitute the major inflammatory cell populations in IgG4-RD lesions. IgG4-RD patients with active, untreated disease show a marked expansion of plasmablasts in the circulation. Although the therapeutic depletion of B cells suggests a role for these cells in the disease, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 64 publications
(66 reference statements)
2
70
0
8
Order By: Relevance
“…Mattoo et al demonstrated oligoclonal expansions of CD4+ effector/memory CTLs within both the blood and the affected tissues of patients with IgG4-RD (87,88). These T cells demonstrated a cytolytic phenotype with expression of SLAMF7, granzyme A, IL-1b, TGF-b1, and IFN-c, cytokines (87). B-cell depletion therapy resulted in both clinical remission and decreased CD4+ CTLs, further implicating these cells in active IgG4-RD (88).…”
Section: Pathophysiologymentioning
confidence: 98%
See 1 more Smart Citation
“…Mattoo et al demonstrated oligoclonal expansions of CD4+ effector/memory CTLs within both the blood and the affected tissues of patients with IgG4-RD (87,88). These T cells demonstrated a cytolytic phenotype with expression of SLAMF7, granzyme A, IL-1b, TGF-b1, and IFN-c, cytokines (87). B-cell depletion therapy resulted in both clinical remission and decreased CD4+ CTLs, further implicating these cells in active IgG4-RD (88).…”
Section: Pathophysiologymentioning
confidence: 98%
“…Recent studies have implicated CD4+ cytotoxic T lymphocytes (CTLs), rather than Th2 responses, in the pathophysiology of the disease (79,87,88). Mattoo et al demonstrated oligoclonal expansions of CD4+ effector/memory CTLs within both the blood and the affected tissues of patients with IgG4-RD (87,88). These T cells demonstrated a cytolytic phenotype with expression of SLAMF7, granzyme A, IL-1b, TGF-b1, and IFN-c, cytokines (87).…”
Section: Pathophysiologymentioning
confidence: 99%
“…IgG4 has neither antibody-dependent cellular cytotoxicity (ADCC) nor complement dependent cytotoxicity (CDC) [42]. Th2 cells and Tregs have been thought to contribute to the pathogenesis of IgG4-RD, but recently Mattoo et al showed that CD4 + cytotoxic T-cells (CD4 + CTLs), follicular helper 2 cells (Tfh2) are mainly associated with the progression of IgG4-RD [43] (Fig. 1).…”
Section: Immunoglobulin-g4-associated Thyroid Diseases Introductionmentioning
confidence: 99%
“…1). IL-4 secreted from Tfh2 cells and possibly from Th2 cells promotes IgG class switching to IgG4, and tumor growth factor (TGF)β produced by immune-mediated cells promotes tissue fibrosis [43]. In the immune reaction, logically, APC should present antigens to T-cells, and thus they may play an important role in the development of IgG4-RD.…”
Section: Immunoglobulin-g4-associated Thyroid Diseases Introductionmentioning
confidence: 99%
“…However, in AIP, an increased number of CD4+ and CD25+ Treg was observed [21,25]. In the most recent reports, attention has been paid to cytotoxic lymphocytes CD4+ (CTLs) [26][27][28][29] as well as the possibility of participation of annexin A11 in the pathogenesis of AIP [30].…”
Section: Pathogenesis Of Igg4-rdmentioning
confidence: 99%